2011
DOI: 10.1111/j.1471-0307.2010.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gum tragacanth, Astragalus gossypinus, addition on stability of nonfat Doogh, an Iranian fermented milk drink

Abstract: In this study, the stabilising property of various concentrations of gum tragacanth in nonfat doogh, an Iranian fermented milk drink, was investigated by measuring phase separation, particle size, flow behaviour and viscoelastic properties. Moreover, light microscopy was used to get more insight into morphological characteristic of protein–polysaccharide complexes in doogh samples. The addition of gum tragacanth improved stabilisation of doogh samples which was associated with an increase in apparent viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…1 Doogh is made by mixing yogurt, water, and a little salt as well as some aqueous extracts of local herbs. Some examples are yogurt drinks in Europe, ker and kumiss in the Middle East, ayran in Turkey and Doogh in Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Doogh is made by mixing yogurt, water, and a little salt as well as some aqueous extracts of local herbs. Some examples are yogurt drinks in Europe, ker and kumiss in the Middle East, ayran in Turkey and Doogh in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It has many benets due to the presence of probiotic and prebiotic microorganisms, which can increase the nutraceutical value of the nal product. 1,6,9 On the other hand, heat treatments such as pasteurization have a key importance in the production of dairy products because this is a common step in the processing of milk products. 2,6,8 Furthermore, a reduction in the amounts of salt and fat can noticeably reduce the physical stability of this dairy beverage.…”
Section: Introductionmentioning
confidence: 99%
“…The conformational parameters of T exuded from Astragalus gossipinus were reported by Mohammadifar et al [17] as follows: 1111 nm for molar mass per unit contour length, 26 nm for persistence length and 1.87 ratio of gyration radius to hydrodynamic radius. Interestingly, previous studies showed that manipulating the interactions between gum tragacanth and milk proteins, which were suggested to be mainly electrostatic, led to improvements in physical stability and texture properties in fermented dairy products [21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…In accordance with the FDA code of Federal Regulation, it is allowed as a food additive (code number E 413 ) at the level of 0.2-1.3% [13]. It has been used since 1961 in the food, 4 pharmaceutical, cosmetic industries due to its perfect resistance to heat and acid [14], high viscosity at low concentration [15], good suspending action and perfect emulsifying and good release properties [16]. It is well known that GT consists of two fractions:…”
Section: Introductionmentioning
confidence: 99%